2022
DOI: 10.1093/ibd/izac167
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Ustekinumab and Anti-TNF Agent as First-Line Biological Therapy in Luminal Crohn’s Disease: A Retrospective Study From 2 Referral Centers

Abstract: Background Real-life data on the efficacy of ustekinumab as first-line therapy for the treatment of luminal Crohn’s disease (CD) compared with anti-tumor necrosis factor (anti-TNF) agents are lacking. We compared the clinical response rates at 3 months in 2 cohorts of biologic-naïve patients treated by ustekinumab and anti-TNF agents. Methods Biologic-naïve patients starting either ustekinumab or an anti-TNF agent for luminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In a retrospective study conducted in two tertiary centers, Rivière et al compared UST with anti-TNF-α drugs in bio-naïve CD patients with luminal disease. The results showed that anti-TNF-α as a first-line treatment was more efficient than UST at three months ( p = 0.02), whereas no difference was detected during a 40-month follow-up ( p = 0.29) [ 84 ]. These findings were probably linked to the effect of IFX rather than ADA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a retrospective study conducted in two tertiary centers, Rivière et al compared UST with anti-TNF-α drugs in bio-naïve CD patients with luminal disease. The results showed that anti-TNF-α as a first-line treatment was more efficient than UST at three months ( p = 0.02), whereas no difference was detected during a 40-month follow-up ( p = 0.29) [ 84 ]. These findings were probably linked to the effect of IFX rather than ADA.…”
Section: Resultsmentioning
confidence: 99%
“…Other treatments are usually recommended for refractory patients or those with specific contraindications to anti-TNF-α drugs [ 108 ]. The real-life data for the use of UST in this setting are still scarce and limited by small sample sizes and large heterogeneity of therapy protocols/outcome definitions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 35 , 45 , 47 , 48 , 55 , 61 , 62 , 63 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Several reports have compared the efficacy and persistence of using anti-TNF-α antibody agents with anti-IL12/23 antibody agents in treating various conditions. 20 , 24 , 25 However, to date, no study has specifically and accurately compared their effectiveness on small intestinal inflammation. Therefore, we aimed to unravel the factors contributing to the improvement in small intestinal endoscopic scores.…”
Section: Discussionmentioning
confidence: 99%